THE ROLE OF STORE AMBIENCE IN MODERN RETAILING (CASE STUDY INFORMA MANADO TOWN SQUARE 3) - Erlangga, Nobian Sari; Tumbuan, Willem J. F. A.; Wangke, Shinta J.C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: In the era globalization, store ambience can be a reason for consumers to be interested and choose the store that they will visit and buy form.  Modern retail business is not only about price but involves other variables related to the value on the customer shopping intention and patronage intention is also known as revisit intention or continuance intention which is the result or outcome of the most important variables in the retail operation. The objective of this research is to find out the role of store ambience in modern retailing at Informa Manado Town Square 3. This research used qualitative analysis. The population in this research refers to the consumers of Informa Manado Town Square 3 and samples used in this study of 15 informants. The results showed some things that greatly affect customer valuation are the presence of cleanliness in the store, good store scent, the right temperature according to customer desires, good lighting settings, the aesthetics of the arrangement of goods based on color and display of well-ordered items. For the patronage intention the possibility of buyers to come shopping again by 50-100%. The Managers of Informa Manado Town Square 3 should pay attention to the presence of music because music is part of the ambience, thereby can increase attractiveness and the amount of interest in buying so that buyers can come again to shop.    Keywords: store ambience, patronage intention, modern retailing, retail